Incidence of Adverse Events Associated With the In-Hospital Transport of Critically Ill Patients. (4th March 2022) - Nonami, Suguru; Kawakami, Daisuke; Ito, Jiro; Ouchi, Kenjiro; Miyoshi, Yusuke; Tatebe, Masao; Tsuchida, Takahiro; Seo, Ryutaro; Mima, Hiroyuki
Abstract : IMPORTANCE: Despite various reports on the incidence of adverse events related to the in-hospital transport of critically ill patients, there is little verification of the correlation between the occurrence of adverse events and the use of checklists. The risk factors for the occurrence of adverse events during transport based on the use of checklists have not been well studied. Understanding them can contribute to making patient transport safer. OBJECTIVES: We aimed to investigate the frequency of adverse events and risk factors related to the in-hospital transport of critically ill patients in a hospital that uses a checklist for transporting patients. DESIGN, SETTING, AND PARTICIPANTS: This single-center, prospective, observational study was conducted between February 1, 2020, and July 31, 2020, at Kobe City Medical Center General Hospital, Japan. Patients greater than or equal to 18 years old who were admitted to the ICU and were transported for examination or procedures were included. MAIN OUTCOMES AND MEASURES: The transport member recorded patient information and any adverse events that occurred and filled out an information collection form. We then applied multivariate analysis to identify risk factors. RESULTS: A total of 117 transports for 117 patients were evaluated in this study. Twenty-two adverse events occurred in 20 transports (17.1%). There were nine transports (7.7%) in which the patients required treatment, all of which were related to patient instability. Multivariate logistic regression analysis showed that the use of sedative drugs was related to adverse events (odds ratio, 2.9; 95% CI, 1.0–8.5; p = 0.04). We were not able to show a relationship of either the severity of the illness or body mass index with the occurrence of adverse events. CONCLUSIONS AND RELEVANCE: This study revealed that the frequency of adverse events related to the in-hospital transportation of critically ill patients based on the use of a checklist was 17.1% and that the use of sedatives was associated with adverse events.